Ausgewählte Werke in Sechs Bänden - Fichte, Johann Gottlieb 1762-1814; Medicus, Fritz 1876-1956 (Darmstadt Wissenschaftlichen Buchgesellschaft, 1962)
This edition of works comprises the most important works of the great philosopher Johann Gottlieb Fichte. It ranges from his early work to his late years and thus sheds light on his intellectual career. The editor Fritz Medicus set himself the goal of reproducing Fichte in a pure and critical manner. In pursuit of this goal, a considerable editing effort was made and the underlying work was text-critically annotated. Then as now, the 'Selected Works in 6 Volumes' by Fritz Medicus are considered to be among the most important editions in Fichte research.
Johann Gottlieb Fichte (1762-1814) was a German philosopher who became a founding figure of the philosophical movement known as German idealism, which developed from the theoretical and ethical writings of Immanuel Kant. Recently, philosophers and scholars have begun to appreciate Fichte as an important philosopher in his own right due to his original insights into the nature of self-consciousness or self-awareness.
Fichte was also the originator of thesis–antithesis–synthesis, an idea that is often erroneously attributed to Hegel.
Keywords: Philosophy